Life beyond pastoralism: livelihood diversification opportunities for pastoralists in Turkana District, Kenya - Watson, D.J.; Binsbergen, J. van (International Livestock Research Institute, 2006)
This report characterises the extent of livelihood diversification in Turkana District, briefly surveys a range of options, identifies their relative strengths and weaknesses, and makes recommendations for supportive interventions by development actors. It relies on three main sources of information: a literature review, key informant interviews, and focus group discussions. A case study approach was used to gain further insights into selected diversification opportunities. The study team, however, noted that, when applying an agreed selection criteria (i.e. showcase the most important livelihood diversification opportunities in operation in Turkana), the case studies had a distinct gender and geographical bias: they were biased towards women's groups and urban centres, Turkwel and Kerio rivers and Lake Turkana. The report discusses drivers for diversification, the main being drought. Then it examines impact of gender and wealth and outlines some potential livelihood diversification options for Turkana District which includes poultry and egg production; trading of small-stock by women's groups; fresh milk, dried milk and dried meat sales; forage trees; collection and sale of wild fruits; aloe production; gum arabic production; charcoal production; ecotourism; gold mining; and casual and waged labour. The brief then presents diversification case studies including honey production and marketing; fishing in Lake Turkana; irrigated agriculture; handicrafts; hides and skins; and small-scale business.